PENYEDERHANAAN FONOLOGIS DALAM PEMEROLEHAN BAHASA PERTAMA: STUDI KASUS ANAK USIA 1;9 - Trisnadewi Komang (Universitas Warmadewa, 2020)
This research was conducted to determine the utterances that can be produced by a child and the simplification process that occurs in the utterances produced. The subject of this study is female twins aged 1 year 9 months. This study uses the method of observation, the researcher observes the two children, records and takes note the words spoken. The researcher participates in communicating with these children. Furthermore, the data that has been obtained in the form of records is transcribed into written form. The list of writings that have been obtained is then identified to find out the simplification process that occurs by comparing with the utterances that should be according to the dictionary and simplification theory in language acquisition. Data that has been analysed are then presented in tabular form and also presented with sentences. The results showed that there were several simplification processes for the utterances produced in the form of substance, reduction and word structure simplification. These two children are able to produce /m/, /k/. /t/, /d/, /p/, /n/, /b/, /a/, /o/,/i/, /É‘Ë/, /e/.